Spontaneous Peritonitis from Perforation of the Colon in Collagenous Colitis. (1st April 2001) - Freeman, HJ; James, D; Mahoney, CJ
Abstract : A 37-year-old woman presented with an acute abdomen following the onset of watery diarrhea. Spontaneous peritonitis was detected, along with evidence of a focal sigmoid colon perforation. Subsequent postoperative colonoscopic studies revealed collagenous colitis with a focal, deep, nongranulomatous ulcer in the sigmoid colon. Although the literature suggests that collagenous colitis tends to have a relatively 'benign' clinical course characterized by chronic or episodic watery diarrhea. Potentially serious and life- threatening complications may occur in this microscopic form of inflammatory bowel disease.